Associations between genetic risk variants for kidney diseases and kidney disease etiology - Wunnenburger, Sebastian; Schultheiss, Ulla T.; Walz, Gerd; Hausknecht, Birgit; Ekici, Arif Bülent; Kronenberg, Florian; Eckardt, Kai-Uwe; Kottgen, Anna; Wuttke, Matthias (Scientific Reports, 2017)
Chronic kidney disease (CKD) is a global health problem with a genetic component. Genome-wide association studies have identified variants associated with specific CKD etiologies, but their genetic overlap has not been well studied. This study examined SNP associations across different CKD etiologies and CKD stages using data from 5,034 CKD patients of the German Chronic Kidney Disease study. In addition to confirming known associations, a systemic lupus erythematosus-associated risk variant at TNXB was also associated with CKD attributed to type 1 diabetes (p = 2.5 × 10(-)(7)), a membranous nephropathy-associated variant at HLA-DQA1 was also associated with CKD attributed to systemic lupus erythematosus (p = 5.9 × 10(-)(6)), and an IgA risk variant at HLA-DRB1 was associated with both CKD attributed to granulomatosis with polyangiitis (p = 2.0 × 10(-4)) and to type 1 diabetes (p = 4.6 × 10(-11)). Associations were independent of additional risk variants in the respective genetic regions. Evaluation of CKD stage showed a significant association of the UMOD risk variant, previously identified in population-based studies for association with kidney function, for advanced (stage >=G3b) compared to early-stage CKD (<=stage G2). Shared genetic associations across CKD etiologies and stages highlight the role of the immune response in CKD. Association studies with detailed information on CKD etiology can reveal shared genetic risk variants.
EVALuna2:4033